How autocrats compete : parties, patrons, and unfair elections in Africa - Morse, Yonatan L. (Cambridge University Press, 2018)
"Preface and Acknowledgements: This book is an examination of the ways by which autocrats compete in unfair elections, and the underlying factors that structure those contests. The ideas that guide it were first discussed in graduate seminars held back in 2007, at a time when terms like competitive and electoral authoritarianism were just coming into vogue. Now, over 10 years later, the initial motivations for this study seem entirely justified, and perhaps more needed than ever. As an era of electoral authoritarianism continues to unfold, to understand the challenges that democracy faces we must also contend with the evolving and complex nature of authoritarian government. This is my modest attempt at shedding some light on these issues, and adding new perspectives on the intersection of authoritarian and electoral politics"--